2013
DOI: 10.5755/j01.eee.19.6.2038
|View full text |Cite
|
Sign up to set email alerts
|

An Improved Dynamic Password-based User Authentication Scheme for Hierarchical Wireless Sensor Networks

Abstract: User authentication is an important issue in wireless sensor networks. Das et al. recently proposed a dynamic password-based user authentication scheme for hierarchical wireless sensor networks, which provides high security and a simple authentication approach. In this paper we present a flaw in Das et al.'s scheme that makes it infeasible for real-life implementation. Additionally, we demonstrate that Das et al.'s scheme has redundant elements. To overcome these imperfections we propose an enhanced user authe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 27 publications
0
39
0
Order By: Relevance
“…2) Compared with the algorithm [2][3][4][5][6][7][8][9], our mechanism provides a way to transmit the secret encrypted message between computers and mobile terminals in both online and offline mode.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…2) Compared with the algorithm [2][3][4][5][6][7][8][9], our mechanism provides a way to transmit the secret encrypted message between computers and mobile terminals in both online and offline mode.…”
Section: Resultsmentioning
confidence: 99%
“…Das [7] used user authentication based on dynamic password encryption in wireless sensor network, and the emulation experiment indicated that the algorithm has high efficiency and security, and the effect of concealing is very good. On the basis of Das"s work, Turkanovic and Holbl [8] proposed an enhanced version of user authentication based on dynamic password encryption. The new authentication strategy overcame some deficiencies in practical use and removed some redundant elements in Das"s method.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…They are both designed to achieve several security requirements such as mutual authentication, password protection, key agreement, resilience against several attacks, and a dynamic node addition phase. Later Xu and Wang [38] and Turkanovic and Hölbl [39] state that Das et al's [36] protocol is imperfection and not applicable for practical implementation and then they both proposed the solution for the improvement. Li et al [40] and Turkanovic and Hölbl [39] also presented some vulnerabilities of Xue et al's [37] protocol and provide better solution.…”
Section: Literature Reviewmentioning
confidence: 99%
“…14 indicates that the protocols [29,36,39] store the key of all the cluster heads of the WSNs into the memory of the smart card. Therefore, the smart card storage cost of specially [29,36,39] is much higher than the related schemes. We have assumed that the length of the identity, password, random number, hash function are 128 bits each.…”
Section: Storage and Communication Cost Comparisonmentioning
confidence: 99%